Appraisal of elementary knowledge and awareness of oral cancer among dental and medical undergraduates - Preeti Sharma; Vijay Wadhwan (Wolters Kluwer Medknow Publications, 2023)
Background: Currently, oral cancer in India ranks among the top three types of cancer affecting mainly the elderly population. However, recent years have witnessed a marked increase in the younger people less than 45 years of age being affected by oral squamous cell carcinoma (OSCC). Thus, its early detection and treatment are of utmost importance and this responsibility lies with the healthcare providers. Therefore, we planned this study to assess the knowledge, attitude and practices of oral cancer among undergraduate dental and medical students. The objective was to suggest strategies to improve awareness on oral cancer. Methods: A pretested questionnaire comprising nineteen questions were distributed among 193 undergraduate dental and 218 undergraduate medical students of our university. Fundamental questions were included in the clinical examination, risk factors and need for information lectures on oral cancer. Chi-square and ANOVA tests were used to analyse the data. Results: The response rate of the study was good with 91.7% (177/193) of the dental and 88% (191/218) of the medical undergraduates participating in the survey. Though dental students had sufficient knowledge regarding the prevention and detection of oral cancer, however, medical students were less aware of the investigative methods of oral cancer. Conclusion: Though the mean knowledge of the dental students was good, they were not confident of diagnosing the early clinical symptoms of oral cancer. Practices on detection of oral cancer have to be reinforced among medical students so that they can contribute to its prevention.